Analisis Problematika Yang Terjadi Pada Putusan Mahkamah Konstitusi Yang Bersifat Final Dan Mengikat: Mahkamah Konstitusi - Syawaludin; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2022)
The decision of the Constitutional Court, which is final and binding, has the meaning that it has been closed to all possibilities for legal remedies thereafter. Consequently, the decision of the Constitutional Court should not be annulled and even ignored. The formulation of the problem raised in this study is, first, What is the meaning of the Constitutional Court's decision which is final and binding? Second, What are the factors that cause problems that occur in the decision of the Constitutional Court which is final and binding? This research is a type of normative legal research, which is an approach carried out based on the main legal material by examining legal theories and laws and regulations related to this research. The results of this study concluded first, the decision of the Constitutional Court is the first and last attempt that has the consequence that no further legal remedies can be taken against the decision, therefore it directly has permanent and binding legal force to be implemented. Second, there are several factors that cause problems that occur in the final decision and bind the Constitutional Court consequently (i) the position of the Constitutional Court only as a negative legislature, (ii) the absence of consequences for the disregard for the decision of the Constitutional Court, (iii) the Constitutional Court does not have an executor unit in charge of guaranteeing the application of the final decision (special enforcement agencies).